ANALISA PENGADAAN ASET TETAP DENGAN MENGGUNAKAN CAPITAL BUDGETING PADA FOTO COPY RESTU IBU - Purwanto, Purwanto; Aina, Muslimatul (JURNAL AKUNTANSI DAN INVESTASI, 2019)
This study aims to analyze the Copy of Restu Ibu in investing or procuring fixed assets in order to maintain the stability of production and produce more copy photos so that consumer demand can be fulfilled. Sources of data in this study are financial statements consisting of statements of income, capital changes, and balance sheets for the period 2013-2017. This type of research is descriptive. The type of data in this study is quantitative data in the form of data relating to financial statements. While the data analysis method used is projection with a linear trend method which is then used to calculate the level of demand in the future. Based on capital budgeting calculations, it can be seen that the results of calculations using projections with linear trend methods, note that the total income in 2018 is Rp. 38,579,500. Then the company will invest in fixed assets in the form of a photo copy machine. Fixed asset investment carried out requires substantial funds so analysis is needed to assess the feasibility of investing through Capital Budgetting techniques. The analysis results show a Payback Period (PP) for 3 years 5 months 7 days which means it does not exceed the investment age of 5 years. Net Present Value (NPV) of Rp. 11,004,111 which means positive. Internal Rate of Return (IRR) is obtained 12.3%> 10% that the procurement can be received. Profitability Index (PI) of 1.45 greater than 1 Based on the analysis of the acquisition of fixed assets, it can be concluded that investment is feasible.